Digital Spatial Profiling of Individual Glomeruli From Patients With Anti-Neutrophil Cytoplasmic Autoantibody-Associated Glomerulonephritis - Ye, Lin; Liu, Yu; Zhu, Xuejing; Duan, Tongyue; Wang, Chang; Fu, Xiao; Song, Panai; Yuan, Shuguang; Liu, Hong; Sun, Lin; Liu, Fuyou; Lee, Kyung; et al. (Frontiers in Immunology, 2022)
We previously showed that the rupture of Bowman’s capsule (BC) promotes the progression of crescentic glomerulonephritis by enhancing the entry of CD8+ T cells into the glomeruli. In the present study, we utilized digital spatial profiling to simultaneously profile the altered mRNA transcript and protein abundances in the glomerular and periglomerular areas of biopsy samples of anti-neutrophil cytoplasmic autoantibody-associated glomerulonephritis (ANCA-GN). The paraffin-embedded biopsy samples were stained with collagen IV, CD45, and Syto13 to distinguish the glomeruli with periglomerular infiltration but intact BC, with focal BC rupture, and with extensive rupture of BC and glomeruli without the crescent formation and leukocytic infiltration in ANCA-GN. By assessing multiple discrete glomerular areas, we found that the transcript expression level of secreted phosphoprotein-1 and its receptor CD44 were upregulated significantly in the glomeruli with more severe ruptures of BC, and their expression levels correlated positively with the fibrotic markers. We also found that both alternative and classic complement pathways were activated in the glomeruli from patients with ANCA-GN. Further, M1 macrophages were involved mostly in the early stage of BC rupture, while M2 macrophages were involved in the late stage and may contribute to the fibrosis process of the crescents. Finally, loss of glomerular cells in ANCA-GN is likely mediated by apoptosis. Our results show that digital spatial profiling allows the comparative analysis of mRNA and protein profiles in the individual glomeruli affected differently by the disease processes and identifies potential novel mechanisms in ANCA-GN.